O papel dos pesqueiros no cotidiano da cidade de São Paulo e na conservação do espaço geográfico - Oliveira, Ronaldo Florido de (2010)
This dissertation had for objective to search the paper of the fishing in the daily one of the City of São Paulo, under the perspective of the conservation of the landscape geographic in a productive model and sustainable of occupation of the ground and the natural resources, in the current and historical time of the fishing urban. In this direction, the study of establishments of the type feefishing , that they had been created in small farms located in surroundings of the São Paulo metropolis, have for purpose, the attainment of data that make possible an analysis of the geographic space, in order to consider the creation of projects that they allow a new use of public and private areas, and that they are come back to the improvement of the ambient quality in the urban centers. For in such a way, data searched had been systemize of way quantitative and qualitative in graphs and tables, what appreciation guaranteed detailed of establishments searched and of its proprietors and frequentadores, what allowing to conclude that these feefishing had started to be a viable alternative for refuncionalização and conservation of urban and agricultural spaces, as much in public areas, as in particular areas